ROE and EVA: How Do They Explain the Degree of Association of Stock Return Models? - Sumiyana Sumiyana; Hendrian Hendrian (The Indonesian Journal of Accounting Research, 2013)
According to empirical theories, in analysis of stock return model, EVA should provide better results than ROE since EVA reflects wealth creation to shareholders. However, this statement is still debatable. While previous studies showed that, either together or separately, they are good indicators, this study raises a new issue that they are actually not as good as we thought. This study investigates the degree of association of stock return model under various ROE and EVA conditions. This study finds that the combination of ROE and EVA could not return a better degree of association. This study also finds that combination of high ROE and high EVA failed to show better degree of association than other combinations. It means that EVA accompanied by ROE could not show the stockholders’ wealth fares. Finally, because of their inconcurrency, this study suggests that they are factually weak and indifferent in their ability to show stockholders’ wealth creation when investigated in a stock return association model.